A topical treatment containing heat‐treated Lactobacillus johnsonii NCC 533 reduces Staphylococcus aureus adhesion and induces antimicrobial peptide expression in an in vitro reconstructed human epidermis model. Issue 4 (8th May 2018) - Rosignoli, Carine; Thibaut de Ménonville, Séverine; Orfila, Danielle; Béal, Méline; Bertino, Béatrice; Aubert, Jérôme; Mercenier, Annick; Piwnica, David
Abstract: Staphylococcus aureus colonization is thought to contribute to the pathophysiology of atopic dermatitis (AD). AD patients exhibit reduced levels of cutaneous antimicrobial peptides (AMPs), which may explain their increased susceptibility to infections. Using an in vitro reconstructed human epidermis (RHE) model, we sought to determine whether topical application of a non‐replicating probiotic, heat‐treated Lactobacillus johnsonii NCC 533 (HT La1), could inhibit S. aureus adhesion to skin and boost cutaneous innate immunity. We found that application of HT La1 suspension to RHE samples reduced the binding of radiolabelled S. aureus by up to 74%. To investigate a potential effect of HT La1 on innate immunity, we analysed the expression of nine AMP genes, including those encoding beta defensins and S100 proteins, following topical application of HT La1 in suspension or in a daily moisturizer lotion. Analysed genes were induced by up to fourfold in a dose‐dependent manner by HT La1 in suspension and by up to 2.4‐fold by HT La1 in the moisturizer lotion. Finally, using ELISA and immunohistochemical detection, we evaluated the expression and secretion of the AMPs hBD‐2 and psoriasin and determined that both proteins were induced by topical HT La1, particularly in the stratum corneum of the RHE. These findings demonstrate that a topically applied, non‐replicating probiotic can modulate endogenous AMP expression and inhibit binding of S. aureus to an RHE model in vitro. Moreover, they suggest that a topical formulation containing HT La1 could benefit atopic skin by enhancing cutaneous innate immunity and reducing S. aureus colonization.